1995
DOI: 10.1111/j.1365-2125.1995.tb05779.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of human chorionic gonadotropin (HCG) in the treatment of obesity by means of the Simeons therapy: a criteria‐based meta‐analysis.

Abstract: 1. A meta‐analysis was conducted to assess if there is scientific ground for the use of human chorionic gonadotropin (HCG) as adjunctive therapy in the treatment of obesity. 2. Published papers relating to eight controlled and 16 uncontrolled trials that measured the effect of HCG in the treatment of obesity were traced by computer‐aided search and citation tracking. 3. The trials were scored for the quality of the methods (based on four main categories: study population, interventions, measurement of effect, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Body weights in the EDP-treated group were not significantly different (p>0.05) compared to the corresponding controls, which was also observed in our earlier study, after estrogen treatment of rats during the neonatal period (17). hCG had no effects on the body weights in this study, and this is in accordance with Lijesen et al (18) who reported that there is no scientific evidence for hCG efficacy in the treatment of obesity. Absolute pituitary weight was significantly increased (p<0.05) only in the EDP-treated animals by 120.0%, in comparison with the controls ( Figure 1B).…”
Section: Resultssupporting
confidence: 93%
“…Body weights in the EDP-treated group were not significantly different (p>0.05) compared to the corresponding controls, which was also observed in our earlier study, after estrogen treatment of rats during the neonatal period (17). hCG had no effects on the body weights in this study, and this is in accordance with Lijesen et al (18) who reported that there is no scientific evidence for hCG efficacy in the treatment of obesity. Absolute pituitary weight was significantly increased (p<0.05) only in the EDP-treated animals by 120.0%, in comparison with the controls ( Figure 1B).…”
Section: Resultssupporting
confidence: 93%
“…The particular weight loss regimen we examined consisted of severe calorie restriction along with vitamin supplements and administration of human chorionic gonadotropin (hCG), a hormone that encourages metabolic utilization of visceral fat reserves 23-26.…”
Section: Introductionmentioning
confidence: 99%
“…A number of controlled clinical trials have been done to evaluate the use of hCG, and these have recently been reviewed (892,893) (Table 20). Lijesen et al (892) evaluated 16 uncontrolled and 8 controlled studies found through a literature search.…”
Section: Human Cg (Hcg)mentioning
confidence: 99%